PENILAIAN KINERJA APARATUR: SEBUAH ANALISIS KEBIJAKAN TERHADAP CAPAIAN KINERJA PEGAWAI: (Studi pada BPS Kabupaten/Kota di Provinsi Papua Barat) - Tahir, Maulana (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2024)
Apparatus Performance Appraisal: A Policy Analysis of Employee Performance Achievements (Study at BPS District/City in West Papua Province). One of the policies carried out by the government to create a professional and prosperous state civil apparatus is to provide performance allowances. In BPS, performance allowances are based on the results of the CKP assessment. However, until now there has been no tool that regulates the procedures and standards for CKP assessment. Based on this, the purpose of this study is to know the implementation of the CKP assessment and conduct a policy analysis to compile alternative CKP assessment policies. This research uses a qualitative approach with informants selected by purposive methods. The results showed that there were differences in the CKP assessment system between BPS Regency/Municipalities in West Papua Province. These differences include the approach used by the appraiser in assessment, the media and document format used. then there is too good a bias that occurs in the CKP assessment. Thus, to create an objective and fair assessment, by conducting a policy analysis, alternative policies can be prepared that can be used in the implementation of the CKP assessment of BPS Regency/Municipalities in West Papua Province.